Corporate identity communication planning: recognition of a sports equipment brand - Kobayashi, Andréa Tiemi; Catto , Camilo; de Castro, Flavia Santos; dos Santos, Geisa Costa (Seven Editora, 2023)
The present work presents communication concepts associated with sports, focusing on the consolidation of the corporate identity of a sports material company. Data were collected on the definition of communication and corporate identity focused on football; information regarding the history of the organization; identification of communication processes; analysis of external and internal environment; mapping of audiences focusing on football clubs sponsored by the organization, in addition to in-depth individual interviews. After that, to illustrate, a communicational diagnosis of a sports material manufacturer was carried out, which supported the elaboration of the objectives and proposed actions with a focus on brand recognition and with the public that it has a relationship. DOI: https://doi.org/10.56238/devopinterscie-082